Исторические предпосылки и теоретические основания синтеза искусств как явления художественной культуры рубежа XIX-XX веков - Кокорина, Е.Г. (Культура народов Причерноморья, 2014)
В данной статье рассматриваются ключевые тенденции развития системы искусства,
которые дополняют и обусловливают друг друга: сохранение видовой обособленности и стремление к
синтезу искусств. Целью работы является анализ предпосылок и оснований для активизации синтеза
искусств на рубеже XIX-XX веков. Противопоставленный художественной разобщённости синтез
становится закономерной особенностью культуры переходного периода, одной из целей которой было
объединение возможностей всех видов искусства. У статті, що пропонується, розглядаються ключові тенденції розвитку системи
мистецтва, які доповнюють та обумовлюють одна одну: збереження видової відособленості й
прагнення до синтезу мистецтв. Метою роботи є аналіз передумов і підстав для активізації синтезу
мистецтв на рубежі XIX-XX століть. Протиставлений художньої роз'єднаності синтез стає
закономірною особливістю культури перехідного періоду, однією з цілей якої було об'єднання
можливостей усіх видів мистецтва. The article is devoted to the key trends in the development of art that complement one another: the
preservation of isolation of each kind of art, the separation of new ones; and tendency of synthesis of arts, their
principles and rules. Both of these trends are fruitful and co-exist throughout the history of culture. Stable
periods are characterized by a gradual development of art in its separate kinds; the inclination for synthesis is a
constructive attempt to find new ways in response to the unstable situation in the culture. The aim of the article
is to analyze the preconditions and foundations of the art synthesis activation at the turn of the 19th-20th
centuries. The synthesis gives the opportunity to get rid of a strict canon, which may limit the creative
realization. Contrasted to art dissociation, the synthesis becomes the naturally determined feature of the
transitional period culture, which aims to bring together all the arts opportunities for integral reality reflection.